Secretory Structures, Histochemistry, and Antibacterial Activity of Macaranga gigantea - Evi Muliyah; Yohana C. Sulistyaningsih; Sulistijorini Sulistijorini; Mohamad Rafi (Postgraduate, University of Mataram, 2023)
Macaranga gigantea is a member of the family Euphorbiaceae. Anak Dalam tribe, an indigenous people that live in Bukit Duabelas National Park Jambi province, used to utilize the bark of M. gigantea to treat diarrhea. This study aimed to identify the secretory structure, histochemical aspects, and antibacterial potency of M. gigantea bark. Microscopic preparations have been made for the observation of secretory structures. Histochemical testing uses Wagner reagent, cupri acetate, ferric trichloride, and aluminum trichloride. Antibacterial activity was tested using the well diffusion method. The type of secretory structure was carried out. M. gigantea bark has idioblast cells as a secretory structure. The idioblast cells are distributed in the cortex. The idioblast cells contain phenolic compounds, alkaloids, and terpenoids. The well diffusion method was used to test different concentrations of bark extracts. According to the findings, M. gigantea bark extracts at 100 mg/mL had the best inhibitory activity against Staphylococcus aureus and Escherichia coli, with a maximal inhibition zone